Inibição da tirosinase e a presença de substâncias bioativas em extratos vegetais: uma revisão integrativa da literatura (Revista Brasileira Multidisciplinar, 2024)
Phenolic acids and C-glycosylated flavonoids have been shown to play a prominent role as tyrosinase inhibitors from natural sources. The present study aimed to perform an integrative review of the literature in order to identify the relationship between tyrosinase inhibition in vitro and the presence of bioactive substances in plant extracts. A systematic search of articles in English was conducted in different databases, between August 2018 and January 2023, using the following descriptors: (tyrosinase) and (inhibitor) and (chlorogenic acid or orientin or isoorientin or rutin or epicatechin) and (plant extracts). The inclusion criteria were: i) studies with tyrosinase-inhibiting plant extracts; ii) studies that evaluated the inhibition of tyrosinase by extracts containing the substances mentioned above; iii) studies evaluating tyrosinase inhibition in vitro. The following exclusion criteria were considered: i) studies that did not identify the presence of bioactive substances; ii) review studies. A total of 42 articles were selected, among which it was found that the aerial parts (n = 26), as well as the methanolic extract (n = 36), were the most used material and plant extract. The most frequently reported substances were chlorogenic acid (n = 40) and rutin (n = 20). The inhibitory capacity of tyrosinase was attributed to a higher dosage of phenolic compounds and flavonoids, as well as the synergistic presence of the substances reported in the present study. It is concluded that the results found are important for the understanding of tyrosinase inhibitor extracts.